IDENTIFIKASI MOLEKULER JENIS-JENIS JAMUR MIKORIZA EKTO YANG BERASOSIASI DENGAN DIPTEROKARPA DI HUTAN HUJAN TROPIKA SEKUNDER - Ulfa, Maliyana; Faridah, Eny; Sumardi; Lee, Su See; Mansor, Patahayah; Roux, Christine le; Galiana, Antoine (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2019)
Many types of soil born fungi associate mutually with high-level plant roots by forming mycorrhiza. While fruit body characterization was used previously, now molecular method wide used to identify ectomycorrhizal fungi when faces discontinuity fruit body presented on the floor and the important of identifying ectomycorrhizal fungi that lignning in particular association.Hence, the purpose of research is to identify the ectomycorrhizal fungi associated with dipterocarp species using moleculer method. Polymerase Chain Reaction (PCR) technique was conducted on DNA extract samples from root tips of dipterocarp trees and 3 (three) Shorea (S. leprosula, S. stenoptera, and S. mecistopteryx) seedlings intentionally planted under mature trees. DNA sequences were amplified using a specific primer pair of fungus and basidiomycetes ITS 1F-ITS 4B. The identity of ectomycorrhizal fungi was obtained by matching DNA sequence of the samples to Genbank database. Molecular identification resulted in 73 genotypes that belong to 13 families, i.e Thelephoraceae, Russulaceae, Clavulinaceae, Sebacinaceae, Inocyabaceae, Amanitaceae, Entolomataceae, Heliotialetaceae, Boletaceae, Cantharellales, Hymenogastraceae, Ceratobasidiceae, and Tricholomataceae. Thelephoraceae consists of 54 genotypes, Russulaceae and Sebacinaceae 13 genotypes, Clavulinaceae 6 genotypes, and the rest consist of 1-3 genotypes. Thelephoraceae is the dominant family in ectomycorrhizal jamurcommunities. Based on the results, it can be concluded that molecular method can be used to identify the real symbiont in mycorrhiza association. In addition, molecular methods can also detect the similarity of ectomycorrhizal fungi that colonizing dipterocarps, both at trees and seedlings level. Keywords :Ectomycorrhizal fungi, Dipterocarp species, Molecular technique, Secondary tropical rain forest